High-quality steel rolling theory and practice - Ginzburg, Vladimir B. (Manufacturing engineering and materials processing, 1993)
Emphasizing solutions to the problems of achieving tight tolerances of important geometrical parameters such as thickness, width, cross-sectional profile, and flatness, this reference focuses on the principles and applications of the latest technology for producing high-quality, flat-rolled steel products.;Illustrated with more than 700 drawings, High-Quality Steel Rolling: defines the geometrical parameters of flat-rolled products in both conventional and standardized forms; clalssifies the various types of transducers and sensors and provides definitions of basic metrological terms; examines thickness and width control in rolling mills, outlining the methods of width change by casting rolling, and pressing; discusses the theoretical aspects of roll deformation, roll thermal expansion, roll wear, and roll bending in relation to strip profile and flatness; reviews various control systems such as roll bending, roll shifting and roll crossing, as well as systems for utilizing rolls with specific profiles and flexible edge rolls; analyzes the main causes of imperfections in the performance of contemporary automatic control systems; and investigates new computer modeling capabilities for resolving problems in product quality.